METODE BARU PRAKIRAAN SIKLUS AKTIVITAS MATAHARI DARI ANALISIS PERIODISITAS - Thomas Djamuluddin (Jurnal Sains Dirgantara, 2005)
Periodicity analysis indicates that sunspot number is better to be used as the base of solar activities prediction. The main periodicity (of about 11 years) is relatively constant so thatit can be used in long-term prediction several cycles ahead. For prediction, wavelet analysis of all domonant periode has to be done on any cycle to be used in reconstructing the cycle pattern and for predicting the next ones. The relationship between length of cycle and maximum amplitude is used to predict the peak of a cycle. Prediction tests of several cycles indicate that this new method is accurate enough in predicting cycle pattern and maximum amplitude several cycles ahead. The ability in predicting several cycles ahead may be the superiority of this method over the precursor method considered to be relatively the most accurate nowadays.